APPLICATION OF A SCIENTIFIC APPROACH TO IMPROVE LEARNING OUTCOMES OF INTRODUCTORY ECONOMICS STUDENTS IN CLASS XI ECONOMICS C2 STATE HIGH SCHOOL 1 MENGWI FOR THE 2023/2024 SCHOOL YEAR - Maria Aventina Nena; Putu Siti Firmani (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2024)
This study aims to find out how the application of a scientific approach can improve the learning outcomes of Economics Tutors for students in class Xl Economics C2 SMAN 1 Mengwi for the 2023/2024 school year. This type of research is a collaborative classroom action research (PTK) designed in two cycles, each cycle consists of three meetings. The subject of this study is students of class Xl C2 SMAN 1 Mengwi for the 2023/2024 Academic Year, which consists of 37 students, consisting of 17 males and 20 females. In this study, the object of research is the application of a scientific approach and learning outcomes of students in class Xl Economics C2 in the odd semester of the 2023/2024 school year, SMAN 1 Mengwi. The achievement of the Minimum Completeness Criterion (KKM) of students in class Xl Economics C2 SMAN 1 Mengwi Experienced an increase in initial observation that only 15 students were able to achieve (KKM), in cycle I In Meeting 1 was categorized. Less (K) In Meeting 2 it is categorized as Sufficient (C) and in cycle II in Meeting 1 it is said to be Enough (C) Meeting 2 is said to be Good (B). Application of the Scientific Approach Model to Improve the Learning Outcomes of Introduction to Economics Class Xl Students of C2 SMAN 1 Mengwi